TEMPERATURE DEPENDENCE OF LUMINESCENCE LIFETIMES OF A-AL2O3:C USING TIME-RESOLVED OPTICAL STIMULATION (FUDMA JOURNAL OF SCIENCES, 2025)
This study reported the performance of a newly developed time-resolved pulsing system by investigating the components of time-resolved optically stimulated luminescence (TR-OSL) signal from carbon-doped aluminium oxide, -Al2O3:C, a material of interest in dosimetry. The study demonstrates time-resolved optical stimulation (TR-OSL) measurements under a brief light-pulse LEDs stimulation. TR-OSL is a technique that separates in time the stimulation and emission of luminescence. In this work, we report the influence of measurement temperature on luminescence lifetimes in -Al2O3:C obtained using a new pulsing system. Luminescence lifetimes were measured from 20C to 140C using a pulsed LED system with a 17 ms stimulation duration. Despite extensive studies on the luminescence properties of -AlO:C, the precise influence of temperature on time-resolved optical stimulation luminescence lifetimes remains insufficiently characterized. Here, we designed and developed a new cost-effective time-resolved pulsing system based on blue LEDs. The measured luminescence lifetimes decreased from 36.8 0.1 ms at 20 0C to 28.0 0.6 ms at 140 0C. Luminescence lifetimes in -AlO:C exhibited thermal quenching at elevated temperatures, attributed to increased non-radiative transitions. The value of the activation energy for thermal quenching for -Al2O3:C was evaluated as 1.02 0.01 eV. The measured activation energy of 1.02 0.01 eV agrees with earlier findings 1.075 1.0 eV reported by Pagonis et al. (Pagonis et al., 2013), 0.96 0.005 eV reported by Ogundare et al. (Ogundare, 2012) and 0.95 0.04 eV by Chithambo et al. (Chithambo, 2014), confirming the thermal quenching model.
Keywords: Time-resolved luminescence; Temperature; Thermal activation energy; Pulsing system; LEDs